2016
DOI: 10.2147/ijn.s110332
|View full text |Cite
|
Sign up to set email alerts
|

The effect of neutral-surface iron oxide nanoparticles on cellular uptake and signaling pathways

Abstract: In recent years, iron oxide nanoparticles (IONPs) have been applied widely to biomedical fields. However, the relationship between the physicochemical properties of IONPs and their biological behavior is not fully understood yet. We prepared 3-methacryloxypropyltrimethoxysilane (MPS)-coated IONPs, which have a neutral hydrophobic surface, and compared their biological behavior to that of Resovist (ferucarbotran), a commercialized IONP formulation modified with carboxymethyl dextran. The rate of MPS-IONP uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“… 34 The spectrum of ferucarbotran differs in this respect in the C-O-C vibrational region, and in the appearance of another peak at 1591 cm −1 , representing the carboxyl functionalization of its dextran shell. 41 Typical peaks of the polyglucose sorbitol carboxymethyl ether coating were detectable in the spectrum of ferumoxytol. 42 For 3T MRI, R 1 , R 2 and R 2 * relaxation rates were measured using different MRI protocols to determine the contrast agent relaxivity values r 1 , r 2 and r 2 * as a measure of in vitro MRI contrast efficiency (see Figure 1C–E ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“… 34 The spectrum of ferucarbotran differs in this respect in the C-O-C vibrational region, and in the appearance of another peak at 1591 cm −1 , representing the carboxyl functionalization of its dextran shell. 41 Typical peaks of the polyglucose sorbitol carboxymethyl ether coating were detectable in the spectrum of ferumoxytol. 42 For 3T MRI, R 1 , R 2 and R 2 * relaxation rates were measured using different MRI protocols to determine the contrast agent relaxivity values r 1 , r 2 and r 2 * as a measure of in vitro MRI contrast efficiency (see Figure 1C–E ).…”
Section: Resultsmentioning
confidence: 97%
“…While the coating of SPION Dex consists of cross-linked dextran, the FTIR spectrum of ferucarbotran showed a less smeared C-O-C vibrational region, indicating the absence of cross-linking, and an appearance of another peak at 1591 cm −1 , representing the carboxyl functionalization of its dextran shell, that contributes to its high surface charge. 41 Also in ferumoxytol, carboxyl groups are responsible for the high negative surface charge. 42 Despite strong differences in surface charge, all three nanoparticle formulations were characterized with a good colloidal stability in aqueous media and blood, which can be attributed to good electrosteric or steric stabilization due to their respective carbohydrate coating.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we developed a novel dual-modality MR/NIRFI nanomicelle by entrapping SPIO nanoparticles into DSPE-PEG5k micelles to which Cy5 and Bom were conjugated. Physical characterization showed that the near-neutral charged nanosized micelles were in the optimum range for enhancing cellular accumulation and biodistribution 38,39. The morphology of nanomicelles also plays a critical role in their cellular fate; spherical nanomicelles, as observed by TEM, show more efficient internalization by tumor cells 40,41…”
Section: Discussionmentioning
confidence: 99%
“…47,50,51,53 For example, Resovist has been designed on the basis of polycrystalline iron oxide MNPs consisting of multiple single crystals coated with carboxydextran with a hydrodynamic size of more than 60 nm in diameter. 54,55 When a weak external field is applied to polycrystalline MNPs, the individual magnetic moment vectors cannot linearly sum due to the availability of antiphase boundaries, resulting in a lower M sat value. 25 Additionally, only MNPs with a diameter of about 30 nm play a significant role in the overall signal generation according to Langevin-theory, which means that only 3% of the total iron mass of the Resovist® solution contributes to the MPI signal.…”
Section: Mnp Designmentioning
confidence: 99%